PROFIL DEMAM BERDARAH DENGUE DI RSUP DR M. DJAMIL PADANG TAHUN 2020-2022 - Yuliza Birman; Pricillia Setiawan; Rendri Bayu Hansah (Nusantara Hasana Journal, 2023)
DHF and Covid-19 may have similar clinical symptoms in the early stages and similar laboratory features. During the Covid-19 pandemic, the possibility of dual infection between Covid-19 and dengue infection should be considered in patients with fever in dengue endemic areas. During the Covid-19 pandemic, dengue cases also increased by more than 71,663 cases with 459 deaths. This study aims to determine the profile of Dengue Hemorrhagic Fever at Dr M. Djamil Hospital, Padang in 2020-2022. This type of research is descriptive using secondary data, namely patient medical records. The study was conducted from June 2021 to April 2022. The affordable population in the study were DHF patients who underwent an examination on the fifth day of fever at RSUP DR. M. Djamil Padang. Sampling by purposive sampling based on inclusion and exclusion criteria in order to obtain a sample of 97 samples. data processing using SPSS version 24.0. Data analysis was carried out univariately and presented in the form of a frequency distribution table. The highest age was adults as many as 53 people (54.6 %), the most gender was male, namely 52 people (53.6%), the highest body temperature was normal, namely 65 people (67%), the highest number of platelets was <100,000 i.e. 88 people (90.7 %), the highest number of leukocytes was 4,000- 10,000, namely 58 people (59.8%), the highest hematocrit value was < 40%, namely 55 people (56.7%), and the highest levels of hemolgobin is normal that is 56 people (57.7%).